Adjuvant therapy for resected colon cancer 2017, including the IDEA analysis. Issue 4 (3rd April 2018) - Tang, Monica; Price, Timothy Jay; Shapiro, Jeremy; Gibbs, Peter; Haller, Daniel G.; Arnold, Dirk; Peeters, Marc; Segelov, Eva; Roy, Amitesh; Tebbutt, Niall; Pavlakis, Nick; Karapetis, Chris; et al.
ABSTRACT: Introduction : Oxaliplatin-based adjuvant chemotherapy has been the standard of care for resected early colon cancer for over a decade. Recent results from the IDEA meta-analysis attempt to address the question of whether 3 or 6 months of adjuvant chemotherapy is preferable in Stage III colon cancer. Areas covered : A review of the literature and recent conference presentations was undertaken on the topic of adjuvant therapy for resected early colon cancers. This article reviews the current evidence for adjuvant treatment of Stage II and III colon cancer, as well as up-to-date data regarding optimal duration of therapy. This article reviews the evidence for lifestyle modifications in the management of early colorectal cancer and other future directions for research in early colon cancer. Expert commentary : In recent years, there have been no advances in the development of novel agents for adjuvant therapy in colorectal cancer. Although the IDEA meta-analysis was negative for its primary non-inferiority endpoint, the detailed results provide valuable information that allows personalisation of treatment regimen and duration.